ANALISA PRESTASI KINCIR AIR TIPE UNDERSHOT YANG BEKERJA PADA SALURAN HORIZONTAL - Rahmad Hidayat Boli; Rifaldo Pido; Mohamad Rival (Universitas Pahlawan Tuanku Tambusai, 2022)
The need for electrical energy has become one of the basic needs for human life, the limitations and capabilities of the state electricity company in providing electricity to the Indonesian people have not been met. Like a village that has not been reached by PLN electricity. The purpose of this study is to determine the output power of a micro hydro power plant using a flat blade, the load variation used is 1 kg to 15 kg, and to determine the characteristics of the waterwheel, then describe the power and efficiency curve using a flat blade on the type Undershot stream. The method used in this research is to measure power efficiency by varying the flow rate of 0.0166 m3/s and 0.0155 m3/s. The flow rate measurement is carried out by filling a bucket with a bucket volume of 20 L. The results obtained in this study are the largest discharge is found at 0.0166 m3/s discharge to get a power of 12.127 Watt, resulting in a waterwheel efficiency of 18.569% at 56 axis rotation 23 rpm. Keyword: Water Wheel, Flat Spoon, Efficiency, Power, Torque